Advocating mixed-methods approaches in health research - MacKenzie Bryers, H; vanTeijlingen, E; Pitchforth, E (Nepal Journal of Epidemiology, 2014)
This methods paper provides researchers in Nepal with a broad overview of the practical and philosophical aspects of mixed-methods research. The three authors have a wide-ranging expertise in planning and conducting mixed-methods studies. The paper outlines the different paradigms or philosophies underlying quantitative and qualitative methods and some of the on-going debates about mixed-methods. The paper further highlights a number of practical issues, such as (a) the particular mix and order of quantitative and qualitative methods; (b) the way of integrating methods from different philosophical stance; and (c) how to synthesise mixed-methods findings. DOI: http://dx.doi.org/10.3126/nje.v4i5.12018 Nepal Journal of Epidemiology 2014; 4(5):417-22